2003
DOI: 10.1128/aem.69.9.5297-5305.2003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting-Enzyme-Inhibitory and Antibacterial Peptides from Lactobacillus helveticus PR4 Proteinase-Hydrolyzed Caseins of Milk from Six Species

Abstract: Sodium caseinates prepared from bovine, sheep, goat, pig, buffalo or human milk were hydrolyzed by a partially purified proteinase of Lactobacillus helveticus PR4. Peptides in each hydrolysate were fractionated by reversed-phase fast-protein liquid chromatography. The fractions which showed the highest angiotensin I-converting-enzyme (ACE)-inhibitory or antibacterial activity were sequenced by mass spectrum and Edman degradation analyses. Various ACE-inhibitory peptides were found in the hydrolysates: the bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(211 citation statements)
references
References 46 publications
5
203
0
3
Order By: Relevance
“…The most abundant peptides are derived from β-CN, reflecting its high susceptibility to plasmin-mediated proteolysis as well as the high content of this casein subunit in HM (14,16). Focusing on bioactive peptides in undigested HM, as shown in Table 1 (14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), two caseinophosphopeptide homologues, a possible opioid peptide or propeptide, and an antibacterial peptide were identified.…”
Section: In Vitro Digestion Of Human Milk Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant peptides are derived from β-CN, reflecting its high susceptibility to plasmin-mediated proteolysis as well as the high content of this casein subunit in HM (14,16). Focusing on bioactive peptides in undigested HM, as shown in Table 1 (14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), two caseinophosphopeptide homologues, a possible opioid peptide or propeptide, and an antibacterial peptide were identified.…”
Section: In Vitro Digestion Of Human Milk Proteinmentioning
confidence: 99%
“…Thus, gastrointestinal digestion would be required for the formation of these shorter bioactive peptide and they would be released from intact β-CN as well as the precursor peptide (residues 51-59). The last bioactive peptide in undigested HM was a peptide of residues 185-211, known as an antibacterial peptide (24). This peptide was also In the amino acid sequence column, peptides in italic indicate possible precursors for bioactive peptides, which include bioactive sequences.…”
Section: β-Cn-derived Bioactive Peptidesmentioning
confidence: 99%
“…Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity ACE-inhibitory peptides are present in the primary structure of various food protein sources including milk proteins [50,69,80,81]. These peptides are also found in fermented camel milk [86].…”
Section: Protection Against Lead Contaminationmentioning
confidence: 99%
“…It has been proposed that it is the milk-derived peptides in fermented milk products that could be a primary factor conferring the antihypertensive effect. In particular, groups of bioactive peptides with properties such as angiotensin-converting enzyme (ACE) inhibition, opioid-like activities, mineral-binding activity, and antithrombotic activity could be associated with the antihypertensive effect (Minervini et al 2003). Although many studies have demonstrated that bioactive peptides in fermented milk can reduce blood pressure (Foltz et al 2007), the molecular mechanisms for this effect are still not clear.…”
Section: Introductionmentioning
confidence: 99%